The Casualties of Greed: Governance Crises, Development Stagnation, and the Quest for Institutional Reforms in Nigeria - Omoyeni, Tolulope Julius; Omotayo, Busuyi Joshua; Onuoha, Anthony Uchenna (Kashere Journal of Politics and International Relations, 2025)
The Nigerian State, Africa's most populous nation, has long struggled with governance crises rooted in corruption, political instability, and systemic inefficiencies. These challenges, largely driven by greed at various levels of government, have resulted in significant developmental stagnation, impeding economic growth, social progress, and the realization of the nation's full potential. This paper examines the intricate relationship between governance failures and their implications for sustainable development in Nigeria, emphasizing the critical role that institutional weaknesses play in perpetuating a cycle of underdevelopment. The study highlights that the true victims of Nigeria’s governance crises are the everyday citizens, who bear the brunt of mismanagement, poor policy decisions, and systemic corruption. Employing a Qualitative Critical Phenomenology (QCP) approach, this research analyzes secondary data, to explore the relationship between elite greed and developmental stagnation. Drawing upon the Conceptual Framework for Nigeria's Governance Crises and Developmental Stagnation, the study investigates how elite greed, ethnic and regional tensions, and institutional weaknesses have contributed to Nigeria's slow pace of development. This paper emphasizes the urgent need for comprehensive systemic reforms that empower citizens to actively engage in governance and demand accountability from their leaders. The paper recommends civic education programs designed to raise awareness of existing accountability frameworks, such as the Freedom of Information (FOI) Act and Whistle-blower Protection laws, enabling citizens especially in rural areas to challenge poor governance.